Stan badań nad przemysłami środkowo-późnoneolitycznymi na Pomorzu Zachodnim - Dziewanowski, Marcin (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
The aim of this paper is to outline the state of research and perspectives of investigations connected with the middle Neolithic and late Neolithic int production in Western Pomerania, seen in terms of the south-western coast of the Baltic Sea cultural tradition. Considerations on int production in these periods result from a noticeable gap in the state of research, that influences one’s perception of the region’s role in the quality of cultural formation, and indirectly it also influences the interpretation of finds, their evaluation dating and cultural attribution. The author`s personal interest in the subject of int technology are the main reasons studying the production and use of multi-side int tools (axes, chisels, and arrowheads). The topic of local production seems to be an especially fruitful direction of research, effects of which show the importance of Western Pomerania in interregional relations. The aim of the conducted studies is also to considerably improve the identification of local raw material and to re-classify the raw int which is found in the region. The present considerations of synthetizing character are recapitulation of the first stage of studies on specificity of the Lower Oder region thorough ages seen in terms of local tradition of int production, basing on local variants of Baltic int. Due to the state of research and character of the available studies on int material from Western Pomerania, the author preliminarily based their work on partly published materials obtained within the last decade. The vision of int production was considerably influenced by many years of observations of materials available in resources of the Archaeology Department of the National Museum in Szczecin, coming from discoveries made before 1945. The presented vision of flint production transformations should be perceived in categories of postulates and research enquires, which should be verified through interdisciplinary, multiaspect studies based on terrain and cabinet research.